Identifikasi Cemaran Eschericia coli pada Daging Babi Segar di Pasar Ruteng, Nusa Tenggara Timur - Yohana Maria Febrizki Bollyn; Roselin Gultom; Maria Tarsisia Luju; Korbianus Feribertus Rinca; Puspita Cahya Achmadi (Politeknik Pembangunan Pertanian Malang, 2023)
Pork is a source of animal protein and the main food ingredient which is always provided in every religious, customary and social activity in East Nusa Tenggara and Manggarai in particular. In Manggarai, pork is traded in many traditional and modern markets, one of which is the Ruteng market. Pork in the Ruteng market is sold in an open place with a location that is not guaranteed for cleanliness so that it can cause bacteria to thrive. One of the microorganisms that can contaminate pork is Escherichia coli. This study aims to identify E. coli contamination in fresh pork sold in the Ruteng market. This research was analyzed with a quantitative descriptive approach. Identification was carried out on 6 samples of pork through planting on EMBA media as an E. coli confirmation test and IMViC test which consisted of SIM test, MRVP test and SCA test. The identification results showed that the six pork samples were positive for Escherichia coli. These results confirm that there is contamination of E. coli bacteria in fresh pork sold at Ruteng Market, East Nusa Tenggara.